1997
DOI: 10.3109/10715769709065778
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of ACE Inhibitors on Ischemia-Reperfusion-induced Arrhythmias in Rats: Is this Effect Related to the Free Radical Scavenging Action of these Drugs?

Abstract: The antiarrhythmic effects of captopril, a sulphydryl-containing angiotensin converting enzyme (ACE) inhibitor, were compared with those of the nonsulphydryl-containing ACE inhibitor lisinopril and the sulphydryl-containing agent glutathione in an in vivo rat model of coronary artery ligation. To produce arrhythmia, the left main coronary artery was occluded for 7 min, followed by 7 min of reperfusion. Captopril (3 mg kg-1) and lisinopril (0.1, 0.3 or 1 mg kg-1) caused marked decreases in mean arterial blood p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Indeed, it has been proposed that ACE inhibitors, such as captopril, that possess sulfhydryl moieties are able to act as scavengers or reactive oxygen species and as a consequence are protective when administered alone (Anderson et al, 1996). However, the picture is complicated by the fact that some ACE inhibitors that do not possess a sulphydryl group have been reported to be cardioprotective in some models (Birincioglu et al, 1997;Matoba et al, 1999). Matoba et al (1999) showed that cilazaprilat, a non-sulfhydryl containing ACE inhibitor, protected directly against hypoxia-reoxygenation injury in cultured rat myocytes and enhanced bradykinin production in the culture media of the myocytes.…”
Section: Ace Inhibitors and The Ischaemic Myocardiummentioning
confidence: 99%
“…Indeed, it has been proposed that ACE inhibitors, such as captopril, that possess sulfhydryl moieties are able to act as scavengers or reactive oxygen species and as a consequence are protective when administered alone (Anderson et al, 1996). However, the picture is complicated by the fact that some ACE inhibitors that do not possess a sulphydryl group have been reported to be cardioprotective in some models (Birincioglu et al, 1997;Matoba et al, 1999). Matoba et al (1999) showed that cilazaprilat, a non-sulfhydryl containing ACE inhibitor, protected directly against hypoxia-reoxygenation injury in cultured rat myocytes and enhanced bradykinin production in the culture media of the myocytes.…”
Section: Ace Inhibitors and The Ischaemic Myocardiummentioning
confidence: 99%
“…ACE inhibitors including captopril have proven to be beneficial in experimental autoimmune encephalomyelitis (Constantinescu et al, 1995), myocarditis (Godsel et al, 2003), adriamycin-induced myocardial and hematological toxicities (O. Al-Shabanah et al, 1998), Freund`s adjuvant arthritis (Agha and Mansour, 2000) and experimental rats` colitis (Jahovic et al, 2005). The ability of captopril to act as a reactive oxygene species (ROS) scavenger (Mira et al, 1993) was found to be of major importance in its protection against ischemia-reperfusion-induced arrhythmias (Birincioglu et al, 1997) and liver injury in rats (Gulluoglu et al, 1996). An anti-tumor, antifibrotic and cytoprotective effects of captopril have also been demonstrated (Williams et al, 2005;Regan et al, 1996;Murley et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Angiotensin-II elevates the release of norepinephrine from terminal adrenergic neurons. 3,4 Moreover, angiotensin-II elevates the release of epinephrine and norepinephrine from adrenal medulla and stimulates the autonomic ganglions in the peripheral autonomic nerve system. 1,4,5 Tyrosine hydroxylase (TH) is an enzyme which plays a central role in neurotransmission and hormonal function of catecholamines.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies have shown that angiotensin-convertingenzyme inhibitors have positive effects on the circulation. Enalapril maleate, which is an angiotensin converting enzyme inhibitor, is used as an antihypertensive drug and blocks angiotensin-I conversion to angiotensin-II [1][2][3] by its action on angiotensin converting enzyme (ACE). [1][2][3] Angiotensin-II elevates the release of norepinephrine from terminal adrenergic neurons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation